Identification of the first glyphosate-resistant wild radish (Raphanus raphanistrum L.) populations - Ashworth, Michael; Walsh, M.; Flower, K.; Powles, S. (John Wiley and Sons Ltd, 2014)
BACKGROUND: In Australia, glyphosate has been used routinely to control wild radish (Raphanus raphanistrum L.) for the past 40 years. This study focuses on two field-evolved glyphosate-resistant populations of wild radish collected from the grainbelt of Western Australia. RESULTS: Two wild radish biotypes were confirmed to be glyphosate resistant by comparing R/S of two suspected populations. Based on R/S from dose-response curves, the R1 and R2 populations were 2.3 and 3.2 times more resistant to glyphosate respectively. Dose response on glyphosate-selected progeny (>1080gha-1) demonstrated that the glyphosate resistance mechanism was heritable. When compared with the pooled mortality results of three known susceptible populations (S1, S2 and S3), the R1 and R2 subpopulations were 3.4-fold and 4.5-fold more resistant at the LD50 level respectively. Both populations were found to have multiple resistance to the phytoene desaturase inhibitor diflufenican, the synthetic auxin; 2,4-D and the ALS inhibitors; chlorsulfuron, sulfometuron-methyl, imazethapyr and metosulam. CONCLUSIONS: This is the first report confirming glyphosate resistance evolution in wild radish and serves to re-emphasise the importance of diverse weed control strategies. Proactive and integrated measures for resistance management need to be developed to diversify control measures away from glyphosate and advance the use of non-herbicidal techniques. © 2014 Society of Chemical Industry.